2004
DOI: 10.1007/s00296-004-0492-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of knee osteoarthritis in Huang-Pu District, Shanghai, China

Abstract: There was a higher proportion of SKOA than AsKOA (72.1% vs 41.6%), and SKOA was significantly more associated with disability (81.0% vs 26.9%, P<0.01). The prevalence of SKOA increased with age, from 1.3% in the 40-49-year-old age group to 13.2% in the 70+ group. Age, body mass index, and female gender were associated risk factors for knee OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 15 publications
4
48
4
Order By: Relevance
“…Although the presence of an osteophyte or cyst, joint space narrowing, and subchondral sclerosis are all considered when determining the radiographic severity, the presence of definite osteophytes, the key feature of K/L Grade 2, is commonly used as the diagnostic criterion of knee OA [7,12,15,25,45]. Based on symptom severity our findings support the appropriateness of the K/L Grade 2 as reflecting clinically important OA.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Although the presence of an osteophyte or cyst, joint space narrowing, and subchondral sclerosis are all considered when determining the radiographic severity, the presence of definite osteophytes, the key feature of K/L Grade 2, is commonly used as the diagnostic criterion of knee OA [7,12,15,25,45]. Based on symptom severity our findings support the appropriateness of the K/L Grade 2 as reflecting clinically important OA.…”
Section: Discussionsupporting
confidence: 69%
“…The K/L scale is the scale most commonly used to evaluate the radiographic severity of knee OA [7,12,15,16,23,25,26,45]. Although the presence of an osteophyte or cyst, joint space narrowing, and subchondral sclerosis are all considered when determining the radiographic severity, the presence of definite osteophytes, the key feature of K/L Grade 2, is commonly used as the diagnostic criterion of knee OA [7,12,15,25,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women had a higher symptomatic OA prevalence than men (9.8% vs. 3.7%, P<0.01). The prevalence of symptomatic OA increased with age, from 1.3% in the 40-49-year-old group to 13.2% in the group aged 70 years and more (23). An exploratory study with a cross-sectional design performed in Poland with a randomly selected study population, including 404 (62.9%) rural women and 238 (37.1%) rural men (total 642), showed that 24.6% of the examined population suffered from joint degenerative disease, and OA was diagnosed in 14.7% of participants.…”
Section: Prevalencementioning
confidence: 99%
“…OA is the most common cause of limitation of activities of daily living after the middle aged. Knee OA, in particular, has a high prevalence in all over the world; recent studies in China show that the prevalence of radiographic knee OA increased according to age (Du et al 2005). The situation is similar in Japan, Korea, and elsewhere (Ikegawa et al 2003;Jin et al 2004).…”
Section: Introductionmentioning
confidence: 71%